Determination of the residential renovation range - Bucoń, Robert; Sobotka, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The article addresses the problem of selecting renovation solution which is a difficult task. It requires the administrator to consider and compare benefits that result from the execution of particular repairs. The priority is to define both the urgency of repair and the financial constraints. Thus, the choice of renovation solution fulfilling these conditions requires a systematic approach. The proposed method allows the decision-maker to assess the state of building, on which basis it is possible to indicate a needed range of renovation – including the information about the level of urgent repairs. During the next stage of calculations, the significance of the selection criteria is defined by means of the fuzzy AHP method. The assessment of these criteria provides the basis for prioritizing and choosing the renovation solutions and is proposed to be conducted by means of TOPSIS method. To illustrate the method, the authors present a numerical example of the proposed approach to selecting renovation solution method applied to a residential building.